A Systematic Review of Sexual and Reproductive Health Knowledge, Experiences and Access to Services among Refugee, Migrant and Displaced Girls and Young Women in Africa - Ivanova, Olena; Rai, Masna; Kemigisha, Elizabeth (International journal of environmental research and public health, 2018)
Adolescent girls and young women are an overlooked group within conflict- or disaster-affected populations, and their sexual and reproductive health (SRH) needs are often neglected. Existing evidence shows that forced migration and human mobility make girls and women more vulnerable to poor SRH outcomes such as high risk sexual behaviors, lack of contraception use, STIs and HIV/AIDS. We performed a systematic literature review to explore knowledge, experiences and access to SRH services in this population group across the African continent. Two databases (PubMed and Web of Science) were searched and from 896 identified publications, 15 peer-reviewed articles published in English met the inclusion criteria for this review. These consisted of eight applied qualitative, five quantitative and two mixed-method study designs. The quality of the studies was evaluated by the mixed-methods appraisal tool (MMAT) using scores in percentages (0–100%). Available evidence indicates that knowledge of young women and girls regarding contraceptive methods, STIs and HIV/AIDS are limited. This population group often experiences gender-based and sexual violence and abuse. The access and availability of SRH services are often limited due to distances, costs and stigma. This review demonstrates that there is still a dearth of peer-reviewed literature on SRH related aspects among refugee, migrant and displaced girls and young women in Africa. The data disaggregation by sex and age should be emphasized for future research in this field
Keywords: sexual and reproductive health; adolescent; refugee; migrant; young women